La cooperación internacional de Grecia - Tselepi, Naya (Revista Española de Desarrollo y Cooperación, 2023)
The integration of Greece in the Development Aid Committee (CAD) in 1999 has brought about fundamental changes in its development policy. The article lays out the main features of Greek foreign policy and its Official Development Aid., focusing on the evolution, the strengths and the weaknesses of the Greek Co-operation system as well as the main DAC’s findings in its “peer-evaluation” of Greece ODA.